40. HISTOPATHOLOGICAL CHARACTERISTICS OF OVARIAN TUMORS SURGERYED AT NGHE AN OBSTETRICS AND PEDIATRIC HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the rate of histopathological types of ovarian epithelial tumors according to the 2020 World Health Organization classification.Subjects and methods: Cross-sectional descriptive study of ovarian epithelial tumor cases at Nghe An Obstetrics and Pediatrics Hospital from January 2021 to September 2024.Results: Among ovarian epithelial tumors, benign tumors accounted for the highest rate of 91.9%, borderline tumors accounted for 5.5% and malignant 2.6%. Serous tumors had the highest number of 178 cases (65.4%), mucinous tumors had 88 cases accounting for 32.4%, endometrioid tumors had only 3 cases of endometrioid carcinoma accounting for 1.1%, mucinous serous tumors and Brenner tumors were rarer, only benign types were found accounting for 0.7% and 0.4%, respectively.Conclusion: Ovarian epithelial tumors are mainly benign. Serous tumors are the most common, followed by mucinous tumors, with other types being less common.
Keywords: histopathological types; Ovarian epithelial tumors